Molecular cloning and characterization of rhesus monkey platelet glycoprotein Iba, a major ligand-binding subunit of GPIb-IX-V complex - Qiao, J.; Shen, Y.; Shi, M.; Lu, Y.; Cheng, J.; Chen, Younan (2014)
Introduction Through binding to von Willebrand factor (VWF), platelet glycoprotein (GP) Iba, the major ligand-binding subunit of the GPIb-IX-V complex, initiates platelet adhesion and aggregation in response to exposed VWF or elevated fluid-shear stress. There is little data regarding non-human primate platelet GPIba. This study cloned and characterized rhesus monkey (Macaca Mullatta) platelet GPIba. Materials and Methods DNAMAN software was used for sequence analysis and alignment. N/O-glycosylation sites and 3-D structure modelling were predicted by online OGPET v1.0, NetOGlyc 1.0 Server and SWISS-MODEL, respectively. Platelet function was evaluated by ADP- or ristocetin-induced platelet aggregation. Results Rhesus monkey GPIba contains 2,268 nucleotides with an open reading frame encoding 755 amino acids. Rhesus monkey GPIba nucleotide and protein sequences share 93.27% and 89.20% homology respectively, with human. Sequences encoding the leucine-rich repeats of rhesus monkey GPIba share strong similarity with human, whereas PEST sequences and N/O-glycosylated residues vary. The GPIba-binding residues for thrombin, filamin A and 14-3-3? are highly conserved between rhesus monkey and human. Platelet function analysis revealed monkey and human platelets respond similarly to ADP, but rhesus monkey platelets failed to respond to low doses of ristocetin where human platelets achieved 76% aggregation. However, monkey platelets aggregated in response to higher ristocetin doses. Conclusions Monkey GPIba shares strong homology with human GPIba, however there are some differences in rhesus monkey platelet activation through GPIba engagement, which need to be considered when using rhesus monkey platelet to investigate platelet GPIba function. © 2014 Elsevier Ltd. All rights reserved.